A "Si‐Locked" Phosphine Oxide Host with Suppressed Structural Relaxation for Highly Efficient Deep‐Blue TADF Diodes. Issue 4 (30th December 2015) - Li, Jing; Ding, Dongxue; Wei, Ying; Zhang, Jing; Xu, Hui
Abstract : Thermally activated delayed fluorescence (TADF) diodes with deep‐blue emission and a state‐of‐the‐art external quantum efficiency are realized by using a novel phosphine oxide host with a high triplet energy of 2.98 eV and a "Si‐locked" planar rigid structure. These results manifest the effectiveness of our "insulating lock" strategy in suppressing structural‐relaxation induced nonradiative energy losses.